Fungsi Intelektual Lanjut Usia di Panti Werdha - Ardiyanti, Sahda Eka; Asri, Yuni; Hastuti, Apriyani Puji; Febriyantie, Yolla Yohanna (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2024)
Background of Study:The elderly period is described as a period of decline, where many changes occur, including a decrease in physical, psychosocial cognitive and intellectual functions. Impact on the decline in daily social activities in the elderly. The purpose of this study was to determine the intellectual function of the elderly at Griya Asih Lawang Werdha Home, Malang Regency.  Methods: This research design is descriptive. The population used was 30 people with total sampling. The variable in this study is the intellectual function of the elderly measured using the SPMSQ questionnaire. Data analysis using percentages then presented in the form of frequency distribution tables. This research was conducted on February 27, 2023 to March 3, 2023 at Panti Wedha Griya Asih Lawang Malang Regency. Results: The results showed that most of the respondents as many as 21 people (70%) experienced damage to intellectual function. Conclusion: most respondents had decreased intellectual function, added age, education and social life affect intellectual function decline.  It is recommended that ways to maintain and control the decline in intellectual function by implementing healthy living behaviors and conducting brain stimulation Keywords: Elderly, Intellectual Function, Nursing Home